Studies on effect of Vitamin E supplementation on antioxidant status and lipid peroxidation in human volunteers - Nadiger, H.A.; Mansur, Mazidah Ahmad (1999)
Effect of supplementation of Vitamin E (Natopherol,400 ill/day) alone or in combination with B-complex for a period of one year on serum levels of MDA (index of lipid peroxidation), total antioxidant status, total cholesterol & HDL cholesterol was studied in 74 male healthy Malay volunteers ranging in age from 18-55 years. Results of the study indicated which is serum MDA levels increase with age without any change in the total antioxidant status which supports the theory that imbalance between oxidative stress and antioxidant status may be involved in aging process, supplementation of Vit E & B-complex reduced serum MDA levels and increased total antioxidant status, E+B administration being superior to E alone, both E alone and E+B administration reduced total cholesterol levels to the same extent, supplementation of E alone did not affect HDL cholesterol levels significantly but E+B administration significantly increased the HDL cholesterol, both E alone and E+B administration reduced the tot. chol.:HDL chol. ratio, the reduction being significantly more with E+B compared to E alone.It is concluded from the study that administration of E+B as opposed toE alone provides better protection against free radical mediated damage. E+B administration may also be more effective in prevention of IHD through their effect on HDL cholesterol levels.